(untitled) (Journal of Bio-Science, 2024)
Congenital heart disease (CHD) is the most common congenital cardiac defect in children. It is a significant cause to infant death and morbidity. This article provides an overview of the etiology and epidemiology of CHD. According to the WHO, Bangladesh has a 6% incidence of congenital heart disease. Nine frequent lesions make up 80% of congenital heart disease. The majority of the rare or complex lesions that make up the remaining 20% of congenital heart disease. The study aims to contribute to overview of CHD enhancing patient outcomes and informing public health policies. This review study employs a systematic review approach to compile and analyze existing research on children with suspected congenital heart disease. We looked at recent studies, and searched pub med, Cochrane database, cardiovascular disease journal. The data mainly involve a review of CHD from various studies of sample groups of different ethnicities; age groups and gender were evaluated. After the application of predefined inclusion/exclusion criteria, 50 studies were included in the systematic review. CHD impacts millions of women worldwide children suffer silently without knowing that there is treatment. CHD are revealed by epidemiology research which must recognize the value of routine medical exams, with the help of successful transition program. A thorough review of the most recent research on the pathophysiology, Incidences clinical symptoms, and therapy of CHD was conducted and optimum care of CHD is essential to enhance the quality of life and prevent the progression of the diseases. J. Bio-Sci. 31(2): 87-101, 2023